Change of the Lithuanian Art (History) Canon: The Late Soviet Period and the Period of Independence - Šapoka, Kęstutis (Sociologija. Mintis ir veiksmas, 2022)
The purpose of this article is to explicate socioideological mechanisms of the Lithuanian art (history) canon of the late Soviet period and the period of independence. It theoretically defines the concept of art (history) canon, an important aspect of which is socioideological predispositions. By drawing on representative publications and albums from the late Soviet period and the period of independence the article analyses how and to what extent the Lithuanian art (history) canon has changed or remained stable. The analysis uses the term ‘Quiet modernism’, which at the end of the first decade of the independence period was used to rebrand the image of Soviet-era artists and re-format the canon. The research showed that, during the time period under investigation, the Lithuanian art (history) canon has been shaped in line with both artistic principles and socioideological factors. The canon has been partly changing, but its core is still inert and static.